Drilling grid blasting upgrading based on Geological Strength Index (GSI), case “La Maruja” mine, Colombia (2016)
Having proper rock masses characterization is of great importance in underground mining works to make the right decisions in terms of sustenance and other tasks like is the case of drilling and blasting. Here it is proposed the built of a geomechanical table based in the GSI through which to decide the drilling grid configuration applies for each rock type. This improves production cycles and explosives consumption in blasting. This table is created from experimental trials in blasting of panels with different drilling grid geometries, the ranging from 60x60cm up 80x80 cm; and the main parameter to ensure is a maximum particle size of 30 cm after the blasting with 24.6% costs reduction.